High-dose influenza vaccine favors acute plasmablast responses rather than long-term cellular responses. Issue 38 (31st August 2016) - Kim, Jin Hyang; Talbot, H. Keipp; Mishina, Margarita; Zhu, Yuwei; Chen, Jufu; Cao, Weiping; Reber, Adrian J.; Griffin, Marie R.; Shay, David K.; Spencer, Sarah M.; Sambhara, Suryaprakash
Highlights: High-dose influenza vaccine induced higher antibody responses in individuals aged ⩾65 years. High-dose influenza vaccine induced higher plasmablast responses. Cell-mediated immunity and memory responses were similar between high and standard-dose vaccine. Abstract: High-dose (HD) influenza vaccine shows improved relative efficacy against influenza disease compared to standard-dose (SD) vaccine in individuals ⩾65 years. This has been partially credited to superior serological responses, but a comprehensive understanding of cell-mediated immunity (CMI) of HD vaccine remains lacking. In the current study, a total of 105 participants were randomly administered HD or SD vaccine and were evaluated for serological responses. Subsets of the group ( n = 12–26 per group) were evaluated for B and T cell responses at days 0, 7, 14 and 28 post-vaccination by flow cytometry or ELISPOT assay. HD vaccine elicited significantly higher hemagglutination inhibition (HI) titers than SD vaccine at d28, but comparable titers at d365 post-vaccination. HD vaccine also elicited higher vaccine-specific plasmablast responses at d7 post-vaccination than SD vaccine. However, long-lived memory B cell induction, cytokine-secreting T cell responses and persistence of serological memory were comparable regardless of vaccine dose. More strategies other than increased Ag amount may be needed to improve CMI in older adults. Trial Registration: ClinicalTrials.govNCT 01189123